(untitled) (Philological Studies, 2019)
Erwin Piscator imagined his political theatre as supporting communism, which he perceived as an alternative to the capitalism of Weimer Germany. Many of Piscator’s performances stage dramatic stories of the subversion of capitalism, advocating an October revolution on the German soil. One of the crucial features of Piscator’s theatre is the use of technology, which is central for his concept of political theatre. One of the most important performances in which Piscator successfully integrated technology into theatre is his “Rasputin”, a piece of theatre which explicitly reflects Piscator’s ideology. The performance deals with the Russian revolution, advocating a global subversion of the regime of capitalism. In addition, Piscator’s “Rasputin” reflects the implications of the use of technology in theatre, and the possible interactions between different media – film and theatre.